Current status of scientific research of nursing students at Hue University of Medicine and Pharmacy - Nguyen, Hoang Long; Tran, Thi Thao; Hoang, Thi Phuong Thao; Pham, Thi Khanh Linh; Ton, Nu Minh Duc; Nguyen, Thi Anh Phuong; Ho, Thi Thuy Trang (Tạp chí Y Dược Huế, 2023)
Background: Experiences of performing scientific research are significantly to enhance nursing evidence- based practice. This study aimed to describe the current status of scientific research of nursing students, and identify attitudes of nursing students toward scientific research at Hue University of Medicine and Pharmacy, Hue University. Materials and methods: Retrospective study and a cross-sectional study design were used. A sample of 47 Bachelor’s thesis in nursing and 516 nursing students at University of Medicine and Pharmacy, Hue University was involved. Data were collected using a questionnaire, which including: (1) General characteristics, (2) “Critical appraisal checklist for cross-sectional study toolkit”, and (3) “The Nursing students’ attitudes towards and awareness of research and development within nursing scale”. Multivariable regression analyses were used to find the associated factors of attitude toward scientific research. Results: Most of undergraduate theses ensure quality assurance in research. Overall, attitude of scientific research among nursing students is moderate. Year of study, ranked academic, read scientific research regularly, and plan to participate in scientific research were significantly associated with attitudes toward scientific research. Conclusion: There is a need to motivate nursing students to participate in scientific activities through provide research and offer opportunities for them to do scientific research.